2006
DOI: 10.1016/j.apcatb.2005.10.027
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of NOx storage on Pt–BaO–Al2O3

Abstract: A series of samples containing 5-wt% or 20-wt% BaO on γ-Al 2 O 3 with different loadings of Pt were prepared and examined for their NO 2 adsorption properties using temperature programmed desorption (TPD), temperature programmed reduction (TPR), and x-ray diffraction (XRD). For calcination at 873 K or above, BaO/Al 2 O 3 formed BaAl 2 O 4. While carbonates were found to be unstable on the aluminate phase, NO 2 reacted with the aluminate to form bulk Ba(NO 3) 2 and Al 2 O 3 , even at room temperature. With BaO/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 27 publications
0
19
1
Order By: Relevance
“…In addition, oxygen desorption peaks were observed over the same temperature range. It has been reported that the nitrate desorption may follow the equation: Ba(NO 3 ) 2 → BaO + 2NO 2 + 1/2O 2 [40]. However, the signal of NO 2 (m/e = 46) in our experiment was very weak and the main desorption feature was NO (m/e = 30) and O 2 (m/e = 32).…”
Section: No X -Tpd Experimentscontrasting
confidence: 48%
“…In addition, oxygen desorption peaks were observed over the same temperature range. It has been reported that the nitrate desorption may follow the equation: Ba(NO 3 ) 2 → BaO + 2NO 2 + 1/2O 2 [40]. However, the signal of NO 2 (m/e = 46) in our experiment was very weak and the main desorption feature was NO (m/e = 30) and O 2 (m/e = 32).…”
Section: No X -Tpd Experimentscontrasting
confidence: 48%
“…Any discussion about the application of these LNTs to realistic cases is not complete without inclusion of CO 2 and H 2 O, which are invariably present in the exhaust of lean burn engines. It is well known that CO 2 and H 2 O result in the presence of carbonate and hydroxide species on Ba which are detrimental to the NO x storage capacity of the traps due to morphological changes in the Ba phase caused by H 2 O and the thermodynamic stability of the surface species resulting in slower NO x adsorption kinetics [1,[10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Many of these studies were performed on samples with various Pt and Ba loadings, at different CO 2 and H 2 O concentrations in the lean feed with various lean-rich cycling protocols, and at a range of operating temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…A typical NSR catalyst consisted of three parts: precious metal as an oxidative and reductive, alkali or alkaline-earth oxide as a storage component and support, for example Pt/BaO/Al 2 O 3 [4][5][6]. Under lean-burn condition, NO was oxidized to NO 2 and stored in the catalyst.…”
Section: Introductionmentioning
confidence: 99%